A review of actuators in ankle-foot rehabilitation therapy - Subramaniam, Krishnan; Shenoy, Rohit; Velu, Vengadeshwaran; Zainuddin, Ahmad Anwar; G Kurappa, Laxamanan; Amirtham, Victor (Penteract Technology, 2022)
Ankle injury is one of the physical injuries that commonly occur during physical related activities, especially in sports. Currently, there are established treatments for ankle rehabilitation at the hospital. This treatment involves range of motion exercises and endurance exercises. However, current treatment requires patients to visit to hospital frequently which is very repetitive in nature. Ankle rehabilitation robots are developed to enhance ankle strength, flexibility and proprioception after injury and promote motor learning and ankle plasticity in patients with drop foot. This article reviews the types of actuators used in ankle rehabilitation and discusses the evolution of industrial robotics towards rehabilitation.